An Optically Controlled Virtual Microsensor for Biomarker Detection In Vivo (Adv. Mater. 47/2022). Issue 47 (24th November 2022) - Zhang, Tiange; Wu, Shuai; Qin, Haifeng; Wu, Huaying; Liu, Xiaoshuai; Li, Baojun; Zheng, Xianchuang
Abstract : Biosensing In article number 2205760, Xiaoshuai Liu, Xianchuang Zheng, and co‐workers introduce an optically controlled virtual microsensor (OCViM) for biomarker detection in vivo. In this new technique, light serves as the virtual handle to manipulate the sensor tip and also excite it to generate fluorescence emission for biosensing. This new technique combines the features of the needle‐type microelectrode and the fluorescence imaging method, leading to significant advantages including noninvasiveness, active control, and high resolution.